Product Lifecycle Management for Society 10th IFIP WG 5.1 International Conference, PLM 2013, Nantes, France, July 6-10, 2013, Proceedings - Bernard, Alain; Rivest, Louis; Dutta, Debasish; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 10th IFIP WG 5.1 International Conference on Product Lifecycle Management, PLM 2013, held in Nantes, France, in July 2013. The 63 full papers presented together with 2 keynote talks were carefully reviewed and selected from 91 submissions. They are organized in the following topical sections: PLM for sustainability, traceability and performance; PLM infrastructure and implementation processes; capture and reuse of product and process information; PLM and knowledge management; enterprise system integration; PLM and influence of/from social networks; PLM maturity and improvement concepts; PLM and collaborative product development; PLM virtual and simulation environments; and building information modeling.
PLM for sustainability, traceability and performance -- PLM infrastructure and implementation processes -- Capture and reuse of product and process information -- PLM and knowledge management -- Enterprise system integration -- PLM and influence of/from social networks -- PLM maturity and improvement concepts -- PLM and collaborative product development -- PLM virtual and simulation environments -- Building information modeling.
Keywords: Computer science; Software engineering; Electronic data processing; Information Systems; Management information systems; Computer Science; Management of Computing and Information Systems; Software Engineering; Information Systems Applications (incl. Internet).; Business Information Systems; Computing Methodologies